Long Term Performance of Some Spurs and Colour Strains of Apple (Malus domestica Borkh.) under Low Altitude Conditions of Kullu Valley of Himachal Pradesh - Kumar, J.; Thakur, Disha; Thakur, Manish (International Journal of Bio-resource and Stress Management, 2023)
The study was undertaken to evaluate the performance of some spur and coloured strains of apple (Malus domestica Borkh.) under low altitude conditions of Kullu valley of Himachal Pradesh. The commercial cultivar Starking delicious introduced in the beginning of the century now does not develop good colour and shape at lower altitude and warmer areas of Himachal Pradesh, due to climate change therefore, two spur cultivars Red Spur and Starkrimsom, four coloured strains Top Red, Vance Delicious, Hardeman and Skyline Supreme Delicious and two spur type pollinizers Stark Spur and Gold Spur grafted on M9 rootstock were compared with commercial cultivar Starking delicious grafted on M9 rootstock at a warmer location Bajaura, Kullu located at an altitude of 1090 m above MSL. The cultivars Vance delicious and Red Spur developed good colour and fruit shape and ripened 11 and 9 days earlier than Starking delicious. Top Red resulted in the highest trunk girth (27.0 cm), shoot growth (17.7 cm) and yield (58.63 t ha-1) for the last five years followed by Vance delicious with trunk girth 26.2 cm , shoot growth 16.1 cm and yield 53.64 t ha-1). It ripened four days earlier to Starking delicious. Other cultivars ripened simultaneously or later than Starking delicious. Vance delicious appeared to be the most suitable cultivar for lower altitude and marginal areas of Himachal Pradesh and has been recommended for commercial cultivation as it performed well under seasonal variation in temperature and rainfall that occurred during the study period.